Heterogeneous catalytic process for the preparation of 2,2,6,6-tetramethyl-4-piperidone

JP7630447B2Active Publication Date: 2025-02-17BASF SE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021569308
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-24
Filing Date
2020-05-24
Publication Date
2025-02-17
Estimated Expiration
2040-05-24

Smart Images

  • Figure 0007630447000005
    Figure 0007630447000005
  • Figure 0007630447000001
    Figure 0007630447000001
  • Figure 0007630447000002
    Figure 0007630447000002
Patent Text Reader

Abstract

The present invention relates to a method for producing 2,2,6,6-tetramethyl-4-piperidone, the method comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, wherein the zeolitic material comprises YO and XO in its framework structure, Y being a tetravalent element and X being a trivalent element, and wherein the molar ratio of YO to XO in the zeolitic material is 16-175; (ii) preparing a reaction mixture comprising acetone and ammonia; and (iii) contacting the catalyst in the reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40-250°C to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone, wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for producing 2,2,6,6-tetramethyl-4-piperidone. [Background technology]

[0002] 2,2,6,6-Tetramethyl-4-piperidone is used as an important intermediate in industrial organic chemistry. Its preparation usually proceeds through a complex system of equilibria in a continuous or semi-continuous process in which acetone is converted with ammonia in the presence of a catalyst. Typically, ammonium salts are used as homogeneous catalysts. The type of conversion can be classified as a cyclocondensation reaction, which releases water. The work-up procedure is usually performed by extraction with caustic soda to remove the water and neutralize the catalyst. The remainder of the acetone is then separated from the organic phase, which is then fractionated.

[0003] Cavani et al. have disclosed a study on the acid-catalyzed condensation of acetone and ammonia to directly produce 2,2,6,6-tetramethyl-4-piperidinone under both homogeneous and heterogeneous conditions, where aqueous ammonia is used as the ammonia source. As a catalyst, HY zeolite with selected characteristics has been investigated. It has been found that by-products are formed during the preparation of 2,2,6,6-tetramethyl-4-piperidone. The by-products may include diacetone alcohol, diacetoneamine, mesityl oxide, 1,2,5,6-tetrahydro-2,2,4,6,6-pentamethyl-pyrimidine, and 2,2,4,6-tetramethyl-2,3-dihydropyridine, the latter being the most undesirable by-product since its formation has been found to be irreversible. According to Cavani et al., 1,2,5,6-tetrahydro-2,2,4,6,6-pentamethyl-pyrimidine can be converted to 2,2,6,6-tetramethyl-4-piperidone by either water insertion and ammonia removal or acetone insertion in the presence of acetone and 2-iminopropane removal. Furthermore, for HY zeolites with different silica to alumina ratios (SAR=6; 15; 200), it was found that the selectivity to 2,2,6,6-tetramethyl-4-piperidone increased with decreasing SAR, whereas the selectivity to the undesirable 2,2,4,6-tetramethyl-2,3-dihydropyridine was highest in the HY zeolite with SAR of 15 and lowest in the HY zeolite with SAR of 6.

[0004] CN107033066 is particularly concerned with a method and special apparatus for the heterogeneous catalytic synthesis of 2,2,6,6-tetramethyl-4-piperidone. As the heterogeneous catalyst, a water-insoluble Lewis acid catalyst, such as an ion exchange resin, a molecular sieve type catalyst, a (doped) metal oxide, a (doped) metal hydroxide, or one or more composite materials of solid organic sulfonic acid, solid organic carboxylic acid, supported metal halide, supported organic ammonium salt, or solid super acid, and acetone can be used. In Example 1, an exchange resin modified with an organic sulfonic acid is used, in Example 2, a molecular sieve supported with ferric chloride is used, in Example 3, a nano-alumina modified catalyst, in Example 4, a nano-alumina modified catalyst and an organic sulfonic acid modified ion exchange resin, in Example 5, a nano-alumina modified catalyst and a molecular sieve catalyst supported with ferric chloride are used. The process involves reacting acetone with ammonia gas using a heterogeneous catalyst in a reaction vessel at 60-75°C for 7 hours, and a water separator is used to separate water from the reaction mixture. After workup, the crude 2,2,6,6-tetramethyl-4-piperidone is purified by rectification. In the disclosed process, ion exchange resins or molecular sieves may be used as Lewis acid catalysts.

[0005] J. Tian et al. have published a study on the effect of HY zeolite on the continuous synthesis of 2,2,6,6-tetramethyl-4-piperidone, where HZSM-5 and H-beta zeolites were also tested. Several different zeolites have been disclosed for the synthesis of 2,2,6,6-tetramethyl-4-piperidone. The most effective zeolite in this regard was found to be HY zeolite with a silica to alumina molar ratio of 11.2, which achieved a conversion of acetone of 46.2% and a selectivity to 2,2,6,6-tetramethyl-4-piperidone of 44.1%. In contrast, H-beta zeolite with a silica to alumina molar ratio of 50 achieved a conversion of acetone of 15.8% and a selectivity to 2,2,6,6-tetramethyl-4-piperidone of 15.3%. Furthermore, the use of H-ZSM-5 zeolite, which has a silica to alumina molar ratio of 50, gave a relatively low conversion (5.6%), with only trace amounts of 2,2,6,6-tetramethyl-4-piperidone being produced. Therefore, for further experiments on reaction conditions, J. Tian et al. considered the use of HY zeolite, which has the lowest relative silica to alumina molar ratio, and did not consider any of the other zeolites. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] F. Cavani et al. in Journal of Molecular Catalysis A: Chemical 393 (2014), 325-332 [Non-Patent Document 2] J. Tian et al. in Journal of Heterocyclic Chemistry 2015, vol. 52, p. 1377-1381 [Patent documents]

[0007] [Patent Document 1] China Patent Application Publication No. 107033066 Summary of the Invention [Problem to be solved by the invention]

[0008] There was therefore a need to develop an improved process for the preparation of 2,2,6,6-tetramethyl-4-piperidone, in which the formation of by-products is avoided or at least reduced.

[0009] It was therefore an object of the present invention to provide an improved process for the preparation of 2,2,6,6-tetramethyl-4-piperidone, in particular with regard to improved selectivity to 2,2,6,6-tetramethyl-4-piperidone, in particular with improved selectivity to 2,2,6,6-tetramethyl-4-piperidone over long reaction times, and therefore in particular to avoid or at least reduce the formation of by-products. [Means for solving the problem]

[0010] Thus, it has been surprisingly found that the use of a catalyst comprising a zeolitic material having a specific silica to alumina molar ratio in a heterogeneous process for the preparation of 2,2,6,6-tetramethyl-4-piperidone improves the selectivity to 2,2,6,6-tetramethyl-4-piperidone and in particular reduces the formation of by-products. Moreover, and in contrast to homogeneous processes, the heterogeneous catalyst is easily separated from the reaction mixture and does not necessarily have to be separated from the reaction mixture, so that the heterogeneous process allows for simple recycling.

[0011] Furthermore, it has been found, quite unexpectedly, that the catalyst does not undergo significant deactivation during the reaction. [Brief description of the drawings]

[0012] [Figure 1]FIG. 2 shows the solid-state 27Al NMR spectrum of the zeolitic material according to Example 1 (top) compared to the zeolitic material of Comparative Example 1 (bottom), where the chemical shift (ppm) is plotted along the abscissa and the relative intensity (arbitrary units) is shown along the ordinate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Accordingly, the present invention provides a method for the preparation of 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure selected from the group consisting of EMT, GME, OFF, FER, HEU, MEL, MWW, RRO, TON, FAU, and mixtures of two or more thereof, wherein the zeolitic material has in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element; 2 and X 2 O 3 is 12 or more; (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0014] It is preferred that the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 8 wt.-% water, more preferably less than 6 wt.-%, more preferably less than 4 wt.-%, more preferably less than 2 wt.-%, more preferably less than 1 wt.-%, more preferably less than 0.5 wt.-%, more preferably less than 0.1 wt.-%, more preferably less than 0.05 wt.-%, more preferably less than 0.01 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0015] The zeolitic material preferably has a framework structure selected from the group consisting of EMT, GME, FER, MWW, FAU and mixtures of two or more thereof, more preferably from the group consisting of FER, FAU and mixtures thereof, more preferably the zeolitic material has the framework structure FAU.

[0016] In one embodiment, the present invention provides a method for preparing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, the zeolitic material having in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element; 2 and X 2 O 3 is 12 or more; (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0017] It is preferable that 5% by weight or more of the catalyst consists of a zeolite material, more preferably 10% by weight or more, more preferably 30% by weight or more, more preferably 50% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 90% by weight or more, more preferably 95 to 100% by weight, preferably 99 to 100% by weight, and more preferably 99.5 to 100% by weight of the catalyst consists of a zeolite material.

[0018] It is preferred that the catalyst is provided as a powder and / or as a moulding, preferably as an extrudate.

[0019] According to the present invention, a shaped object is to be understood as a three-dimensional entity resulting from a molding process, therefore the term "shaped object" is used synonymously with the term "shaped body".

[0020] It is preferred that Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, preferably Y is Si and / or Ti, more preferably Y is Si.

[0021] It is preferred that X is selected from the group consisting of B, Al, Ga, In, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and mixtures of two or more thereof, preferably from the group consisting of B, Al, Ga, In, and mixtures of two or more thereof, preferably X is Al and / or B, more preferably X is Al.

[0022] In another embodiment, the present invention provides a method for preparing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, the zeolitic material having in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element;2 and X 2 O 3 The molar ratio of is 16 to 175. (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0023] YO contained in zeolite materials 2 and X 2 O 3 YO 2 and X 2 O 3 No particular restrictions apply regarding the molar ratio of YO to zeolite material. 2 and X 2 O 3 It is preferable that the molar ratio of to is 13 or more, more preferably in the range of 13 to 300, preferably in the range of 14 to 250, more preferably in the range of 15 to 200, more preferably in the range from FNMR, more preferably in the range of 17 to 150, more preferably in the range of 18 to 125, more preferably in the range of 19 to 100, more preferably in the range of 20 to 90, more preferably in the range of 21 to 80, more preferably in the range of 22 to 70, more preferably in the range of 22.5 to 60, more preferably in the range of 23 to 50, more preferably in the range of 23.5 to 45, more preferably in the range of 24 to 40, more preferably in the range of 24.5 to 37, more preferably in the range of 25 to 35, and more preferably in the range of 25 to 30.

[0024] As disclosed above, it is preferred that the zeolitic material has the FAU framework structure type. When the zeolitic material has the FAU framework structure type, the zeolitic material has from the group consisting of Li-LSX, zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, SAPO-37, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof; More preferably, from the group consisting of zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, More preferably, from the group consisting of zeolite X, zeolite Y, ZSM-20, ZSM-3, faujasite, and mixtures of two or more thereof, More preferably, the group consisting of zeolite X, zeolite Y, faujasite, and mixtures of two or more thereof. Contains one or more zeolites having a selected FAU-type framework structure, More preferably, the one or more zeolites having an FAU-type framework structure comprise zeolite X and / or zeolite Y, preferably zeolite Y; More preferably, the one or more zeolites having an FAU-type framework structure are zeolite X and / or zeolite Y, preferably zeolite Y.

[0025] It is preferred that the zeolitic material is in the ammonium or H form, more preferably the H form.

[0026] No particular restrictions apply with regard to the chemical or physical properties of the zeolitic material. The zeolitic material is preferably capable of temperature programmed desorption of ammonia (NH 3-TPD) [according to Reference Example 2], it is preferable that the acid site concentration is within the range of 0.100 to 4.000 mmol / g at a temperature in the range of 190 to 550°C, more preferably within the range of 0.200 to 2.000 mmol / g at a temperature in the range of 205 to 400°C, more preferably within the range of 0.250 to 1.000 mmol / g at a temperature in the range of 250 to 290°C, more preferably within the range of 0.300 to 0.800 mmol / g at a temperature in the range of 350 to 375°C, and more preferably within the range of 0.400 to 0.700 mmol / g at a temperature in the range of 360 to 366°C.

[0027] Temperature programmed desorption of ammonia (NH 3 -TPD) is carried out in an automatic chemisorption analysis unit (Micromeritics AutoChem II 2920) with a thermal conductivity detector. A continuous analysis of the desorbed species is carried out using an online mass spectrometer (OmniStar QMG200 from Pfeiffer Vacuum). The sample (0.1 g) is introduced into a quartz tube and analyzed using the following program: The temperature is measured by a Ni / Cr / Ni thermocouple located just above the sample in the quartz tube. He of purity 5.0 is used for the analysis. Before every measurement, a blank sample is analyzed for calibration.

[0028] 1. Preparation: Start recording, one measurement per second. 25°C and 30cm 3 Wait for 10 minutes at room temperature (approximately 25°C and 1 atm), heat to 600°C at a heating rate of 20 K / min, and maintain for 10 minutes. 3 / min) to 100 °C at a cooling rate of 20 K / min (furnace temperature gradient), and then cooled with a He flow (30 cm 3 / min) to 100 °C at a cooling rate of 3 K / min (sample temperature ramp). 2. NH 3 Saturation by: Start of recording, one measurement per second. Gas flow: 100 °C, 10% NH in He 3 (75cm 3 / min; 100°C and 1 atm) and maintained for 30 min. 3. Remove excess: Start recording, take one measurement per second. Gas flow at 100°C, 75cm 3 / min (100°C and 1 atm) and maintained for 60 min. 4. NH 3 -TPD: Start of recording, one measurement per second. He flow (flow rate: 30 cm 3 / min) to 600 °C at a heating rate of 10 K / min and maintained for 30 min. 5. End of measurement.

[0029] The desorbed ammonia was measured by an online mass spectrometer, which demonstrated that the signal from the thermal conductivity detector was caused by the desorbed ammonia. This involved using the m / z=16 signal from ammonia to monitor the desorption of ammonia. The amount of adsorbed ammonia (mmol per g of sample) was ascertained by integrating the TPD signal with a horizontal baseline using Micromeritics software.

[0030] Furthermore, the zeolitic material is preferably capable of temperature programmed desorption of ammonia (NH 3 As determined by HPLC (HPLC-TPD), it is preferred that the acid site concentration is in the range of 0.050 to 0.600 mmol / g at a temperature in the range of 175 to 210°C, and more preferably in the range of 0.140 to 0.530 mmol / g at a temperature in the range of 185 to 200°C.

[0031] Furthermore, the zeolitic material is preferably capable of temperature programmed desorption of ammonia (NH 3 As determined by FT-TPD (times constant phase deviation), it is preferred that the acid site concentration is in the range of 0.010 to 0.090 mmol / g at a temperature in the range of 475 to 625°C, and more preferably in the range of 0.030 to 0.060 mmol / g at a temperature in the range of 500 to 600°C.

[0032] It is preferred that the zeolitic material has a degree of crystallinity in the range of 50-100% by weight, more preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 90-100% by weight, the degree of crystallinity preferably being determined as described in Reference Example 3.

[0033] It is preferred that the zeolitic material has a degree of crystallinity in the range of 50-100 wt%, more preferably 75-100 wt%, more preferably 80-100 wt%, more preferably 90-100 wt%, and the degree of crystallinity is preferably determined by powder X-ray diffraction (PXRD) using a diffractometer (D8 Advance Series II, Bruker AXS GmbH) equipped with a LYNXEYE detector operated with a copper anode X-ray tube operated at 40 kV and 40 mA. The geometry is Bragg-Brentano type and air scattering is reduced using an air scattering shield. The crystallinity of the samples is determined using the software DIFFRAC.EVA supplied by Bruker AXS GmbH, Karlsruhe. The phase composition is calculated on the raw data using the modeling software DIFFRAC.TOPAS supplied by Bruker AXS GmbH, Karlsruhe. The crystal structure of the identified phases, the instrumental parameters and the crystallite sizes of the individual phases are used to simulate the diffraction pattern. This is fitted to the data in addition to a function modeling the background intensity. The sample is homogenized in a mortar and then pressed into a standard flat sample holder supplied by Bruker AXS GmbH for Bragg-Brentano geometry data collection. A glass plate is used to compress and flatten the sample powder to obtain a flat surface. The variable divergence slit is set at an angle of 0.1° to collect data from an angle range of 2-70° 2θ with a step size of 0.02° 2θ. The crystalline content represents the intensity of the crystalline signal relative to the total scattering intensity.

[0034] It is preferred that the zeolitic material has a volumetric particle size distribution characterized by a Dv50 value in the range of 4.0 to 7.0 micrometers, more preferably in the range of 4.5 to 6.5 micrometers, more preferably in the range of 5.0 to 6.0 micrometers.

[0035] YO calculated as element Y contained in the zeolite material 2 No specific restrictions apply regarding the content of YO calculated as element Y. 2 is preferably contained in the zeolite material in an amount within a range of 35.0 to 47.0% by weight, more preferably within a range of 38.5 to 43.5% by weight, and more preferably within a range of 40.0 to 42.0% by weight, based on the total weight of the zeolite material.

[0036] X is calculated as the X contained in the zeolite material 2 O 3 No specific restrictions apply regarding the content of X calculated as X 2 O 3 is preferably contained in the zeolite material in an amount within a range of 1.0 to 4.5% by weight, more preferably within a range of 2.2 to 3.7% by weight, and more preferably within a range of 2.9 to 3.3% by weight, based on the total weight of the zeolite material.

[0037] The zeolite material is preferably 380 ml, determined as described in Reference Example 1. 2 / g or more, more preferably 650m 2 / g or more, more preferably 700 to 800m 2 It is preferable that the carbon black has a BET specific surface area in the range of 1 / g.

[0038] The zeolitic material preferably has a molecular weight of 380 m, determined by nitrogen physisorption at 77 K according to the method disclosed in DIN 66131. 2 / g or more, more preferably 650m 2 / g or more, more preferably 700 to 800m 2 It is preferable that the carbon black has a BET specific surface area in the range of 1 / g.

[0039] The zeolite material is preferably 500 ml 2 / g or more, more preferably 800m 2 / g or more, more preferably 810 to 1100m 2 It is preferable that the Langmuir specific surface area is in the range of 1 / g.

[0040] As disclosed above, it is preferred that X comprises (preferably is) Al. When X comprises (preferably is) Al, the solids of the zeolitic material, preferably determined as described in Reference Example 4, are 27 It is preferred that Al NMR shows a peak in the range of 80-40 ppm and a peak in the range of 40-15 ppm, where the ratio of the peak integral of the peak in the range of 80-40 ppm to the peak integral of the peak in the range of 40-15 ppm is at least 3:1, more preferably at least 7:1, more preferably at least 10:1.

[0041] As disclosed above, it is preferred that X comprises (preferably is) Al. When X comprises (preferably is) Al, it is preferably 27 The solid-state properties of zeolite materials as determined by Al solid-state nuclear magnetic resonance (NMR) 27 It is preferred that Al NMR shows a peak in the range of 80-40 ppm and a peak in the range of 40-15 ppm, and the ratio of the peak integral of the peak in the range of 80-40 ppm to the peak integral of the peak in the range of 40-15 ppm is at least 3:1, more preferably at least 7:1, more preferably at least 10:1.

[0042] 27 Solid-state nuclear magnetic resonance (NMR) was performed using samples stored at 62% relative humidity for at least 60 hours prior to packing; 3.2 mm ZrO 2 Loading of the sample into the rotor, Bruker Avance Neo spectrometer with 14.1 Tesla magnet, 15 kHz (ω / 2π) magic angle spinning, AlCl 3 Solution (1%, H2 One-pulse radio frequency excitation, corresponding to a 0.92 μs, 15° pulse in O; 10 ms acquisition of free induction decay, heterogeneous nuclei 1 H without high frequency decoupling, averaging of at least 5120 scans with 0.5 s recycle delay, Fourier transformation with 10 Hz exponential line broadening for noise suppression, manual phasing and baseline correction in Bruker Topspin 3.0. 37.77 ppm as secondary standard according to Pure Appl. Chem., Vol. 80, No. 1, pp. 59-84, 2008. 13 Using adamantane with a C methylene resonance, the frequency ratio of D is 0.26056859 on the absolute chemical shift scale. 2 1.1 mol / kg Al(NO 3 ) 3 The spectrum is referenced to the standard.

[0043] Furthermore, when X comprises Al (preferably is Al), the solids of the zeolitic material, determined as described in Example 4, are preferably 27 It is preferred that Al NMR shows a peak in the range of 80-40 ppm and a peak in the range of 15-20 ppm, and the ratio of the peak integral of the peak in the range of 80-40 ppm to the peak integral of the peak in the range of 15-20 ppm is at least 3:1, more preferably at least 7:1, more preferably at least 10:1.

[0044] It is preferred that the zeolitic material has a micropore volume, preferably determined as described in Reference Example 1, in the range of 0.180 to 0.390 ml / g, more preferably in the range of 0.220 to 0.350 ml / g, more preferably in the range of 0.260 to 0.310 ml / g.

[0045] The zeolitic material preferably has an average pore size, preferably determined as described in Reference Example 1, in the range of 4.0 to 18.0 nm, more preferably in the range of 5.5 to 8.0 nm, more preferably in the range of 6.6 to 7.3 nm.

[0046] It is preferred that the zeolitic material has an average pore width, preferably determined as described in Reference Example 1, in the range of 1.5 to 5.5 nm, more preferably in the range of 2.0 to 3.5 nm, more preferably in the range of 2.4 to 2.8 nm.

[0047] It is preferred that the zeolite material prepared in (i) is a calcined zeolite material, and has been calcined at a temperature within the range of 300 to 900°C, more preferably within the range of 400 to 700°C, more preferably within the range of 450 to 650°C, and more preferably within the range of 500 to 600°C.

[0048] The calcination time should be adjusted according to the mass of the precursor of the molded product to be calcined. The zeolite material is preferably calcined for 0.5 to 24 hours, more preferably 1 to 15 hours, more preferably 2 to 12 hours, more preferably 2.5 to 9 hours, more preferably 3 to 7 hours, more preferably 3.5 to 6.5 hours, more preferably 4 to 6 hours.

[0049] No particular restrictions apply with regard to further steps. It is preferred to wash the catalyst with acetone before contacting it with the reaction mixture of (ii). It is preferred to first contact the catalyst with acetone before contacting it with the reaction mixture of (ii).

[0050] No particular restriction applies with respect to the temperature at which the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out. It is preferred that the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out at a temperature in the range of 45 to 200°C, more preferably 50 to 150°C, more preferably 55 to 120°C, more preferably 60 to 100°C, more preferably 65 to 90°C, more preferably 70 to 80°C.

[0051] No particular restrictions apply with regard to the pressure at which the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out. It is preferred that the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out at a pressure in the range of 1 to 200 bar (abs), more preferably in the range of 20 to 150 bar (abs), more preferably in the range of 30 to 100 bar (abs), more preferably in the range of 45 to 80 bar (abs), more preferably in the range of 50 to 70 bar (abs), more preferably in the range of 55 to 65 bar (abs).

[0052] As disclosed above, no particular constraints apply with respect to the pressure at which the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out. It is preferred that the step of contacting the catalyst with the reaction mixture prepared in (ii) in (iii) is carried out at a pressure in the range of 1 to 30 bar (abs), more preferably in the range of 1 to 20 bar (abs), more preferably in the range of 1 to 15 bar (abs), more preferably in the range of 1 to 10 bar (abs), more preferably in the range of 1 to 5 bar (abs), more preferably in the range of 1 to 3 bar (abs).

[0053] The process is preferably carried out as a batch process or as a continuous process, and it is particularly preferred that the process is carried out as a continuous process.

[0054] As disclosed above, the process is preferably carried out as a continuous process. When the process is carried out as a continuous process, the contacting step in (iii) is preferably carried out at a liquid hourly space velocity (LHSV) in the range of 0.01 to 1000 ml / (g·h), more preferably 0.05 to 500 ml / (g·h), more preferably 0.1 to 250 ml / (g·h), more preferably 0.3 to 100 ml / (g·h), more preferably 0.5 to 10 ml / (g·h), more preferably 1 to 5 ml / (g·h), more preferably 1.2 to 4 ml / (g·h), more preferably 1.5 to 3 ml / (g·h), more preferably 1.8 to 2.5 ml / (g·h), more preferably 2.0 to 2.2 ml / (g·h).

[0055] As disclosed above, the method may include the further steps of: (iv) separating 2,2,6,6-tetramethyl-4-piperidone from the reaction product to obtain 2,2,6,6-tetramethyl-4-piperidone and a residual mixture; (v) recycling at least a portion of the residual mixture in the reaction mixture of (ii). and preferably after (iv) and before (v) compounds having a boiling point higher than that of 2,2,6,6-tetramethyl-4-piperidone are separated from the remaining mixture.

[0056] No particular restriction is applied regarding the molar ratio of acetone to ammonia in the reaction mixture prepared in (ii). It is preferred that the molar ratio of acetone to ammonia in the reaction mixture prepared in (ii) is within the range of 5:1 to 25:1, more preferably 7:1 to 22:1, more preferably 10:1 to 19:1, more preferably 13:1 to 16:1, more preferably 14.0:1.0 to 14.7:1.0, more preferably 14.2:1.0 to 14.5:1.0.

[0057] As disclosed above, the process may be carried out as a batch process. When the process is carried out as a batch process, it is preferred that the contacting step in (iii) is carried out for a period of time in the range of 0.1 to 24 hours, more preferably in the range of 0.5 to 20 hours, more preferably in the range of 1 to 15 hours, more preferably in the range of 3 to 10 hours, more preferably in the range of 4 to 8 hours, more preferably in the range of 5 to 7 hours.

[0058] As disclosed above, the catalyst may be provided as a molding. When the catalyst is provided as a molding, the molding may include: (a) preparing a mixture comprising a zeolitic material and optionally one or more binders; (b) shaping the mixture, preferably by extrusion, to obtain a shaped material; (c) optionally drying the shaped material in a gas atmosphere; (d) sintering the shaped material obtained from (b) or (c) in a gas atmosphere to obtain a shaped product. It is preferably prepared according to a method comprising:

[0059] As disclosed above, when the method comprises (a), (b), (c) and (d), it is preferred that the mixture comprises one or more binders, and that the one or more binders are one or more of alumina, silica, silica-alumina, graphite, polysaccharides, sugar alcohols and synthetic polymers, more preferably one or more of alumina, silica, silica-alumina, graphite, sugar alcohols, synthetic polymers, cellulose, modified cellulose and starch, more preferably silica, alumina, silica-alumina, graphite, sugar alcohols, synthetic polymers, microcrystalline cellulose, cellulose ethers, more preferably graphite, sorbitol, mannitol, polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), hydroxypropyl cellulose (HPC), hydroxypropyl methylcellulose (HPMC) and sodium carboxymethylcellulose.

[0060] When the method comprises (a), (b), (c), and (d) as disclosed above, it is further preferred that in the mixture according to (a), the weight ratio of the one or more binders to the zeolitic material is in the range of 1:10 to 1:30, more preferably in the range of 1:15 to 1:25.

[0061] When the method comprises steps (a), (b), (c) and (d) as disclosed above, the method further comprises a step of drying according to (c) preferably carried out in a gas atmosphere having a temperature in the range of 90-150°C, more preferably at a temperature in the range of 110-130°C, for preferably 10-15 hours, more preferably 11-13 hours.

[0062] As disclosed above, when the method includes (a), (b), (c), and (d), it is further preferred that the gas atmosphere of (d) has a temperature in the range of 400 to 600°C, more preferably in the range of 450 to 550°C, and that the firing is preferably performed for 3 to 7 hours, more preferably 4 to 6 hours.

[0063] When the method comprises (a), (b), (c), and (d) as disclosed above, it is further preferred that the gas atmosphere in one or more of (c) and (d) comprises one or more of nitrogen, oxygen, and argon, preferably nitrogen.

[0064] Within the meaning of the present invention, a specific value of relative humidity is not particularly limited with respect to an atmosphere exhibiting said specific value of relative humidity, as in principle the value relates to any suitable atmosphere exhibiting said value of relative humidity, for example an atmosphere of air or an inert gas (for example nitrogen, argon or mixtures thereof). However, according to the present invention, the specific relative humidity preferably refers to the relative humidity of an atmosphere selected in the group consisting of air, nitrogen, argon and mixtures of two or more thereof, more preferably the specific relative humidity refers to a nitrogen and / or argon atmosphere exhibiting said level of relative humidity, more preferably a nitrogen atmosphere exhibiting said specific level of relative humidity.

[0065] According to the present invention, a moulding is to be understood as a three-dimensional entity resulting from a moulding process; the term "moulding" is therefore used synonymously with the term "molded body".

[0066] The unit bar (abs) is 10 5 The unit of pressure is 10 Pa. -10 Refers to the length of m.

[0067] The present invention is further described by the following series of embodiments and combinations of embodiments resulting from the dependent and back references as described. In particular, in each case where a range of embodiments is mentioned, it is noted that in the context of a term such as "any one of the methods of embodiments 1 to 4", any embodiment within this range is intended to be clearly disclosed to a person skilled in the art, that is, the expression of this term should be understood by a person skilled in the art as being synonymous with "any one of the methods of embodiments 1, 2, 3, and 4". Furthermore, it is clearly noted that the following series of embodiments represents a properly organized part of the description directed to the general and preferred aspects of the present invention, rather than a series of claims that determine the degree of protection.

[0068] 1. A method for producing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure selected from the group consisting of EMT, GME, OFF, FER, HEU, MEL, MWW, RRO, TON, FAU, and mixtures of two or more thereof, wherein the zeolitic material has in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element; 2 and X 2 O 3 is 12 or more; (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, The process wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture, preferably less than 8 wt.-%, more preferably less than 6 wt.-%, more preferably less than 4 wt.-%, more preferably less than 2 wt.-%, more preferably less than 1 wt.-%, more preferably less than 0.5 wt.-%, more preferably less than 0.1 wt.-%, more preferably less than 0.05 wt.-%, more preferably less than 0.01 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0069] 2. The method according to embodiment 1, wherein the zeolitic material has a framework structure selected from the group consisting of EMT, GME, FER, MWW, FAU, and mixtures of two or more thereof, preferably FER, FAU, and mixtures thereof, more preferably FAU.

[0070] 3. The method according to embodiment 1 or 2, wherein at least 5% by weight of the catalyst consists of a zeolite material, preferably at least 10% by weight, more preferably at least 30% by weight, more preferably at least 50% by weight, more preferably at least 70% by weight, more preferably at least 80% by weight, more preferably at least 90% by weight, more preferably from 95 to 100% by weight, preferably from 99 to 100% by weight, more preferably from 99.5 to 100% by weight of the catalyst consists of a zeolite material.

[0071] 4. The method according to any one of the preceding embodiments, wherein the catalyst is provided as a powder and / or as a moulded product, preferably as an extrudate.

[0072] 5. The method of any one of the preceding claims, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof, preferably Y is Si and / or Ti, more preferably Y is Si.

[0073] 6. The method according to any one of the preceding claims, wherein X is selected from the group consisting of B, Al, Ga, In, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and mixtures of two or more thereof, preferably from the group consisting of B, Al, Ga, In, and mixtures of two or more thereof, preferably X is Al and / or B, more preferably X is Al.

[0074] 7. YO of Zeolite Materials 2 and X 2 O 3 is 13 or more, preferably in the range of 13 to 300, preferably in the range of 14 to 250, more preferably in the range of 15 to 200, more preferably in the range of 16 to 175, more preferably in the range of 17 to 150, more preferably in the range of 18 to 125, more preferably in the range of 19 to 100, more preferably in the range of 20 to 90, more preferably in the range of 21 to 80, more preferably in the range of 22 to 70, more preferably in the range of 22.5 to 60, more preferably in the range of 23 to 50, more preferably in the range of 23.5 to 45, more preferably in the range of 24 to 40, more preferably in the range of 24.5 to 37, more preferably in the range of 25 to 35, and more preferably in the range of 25 to 30.

[0075] 8. A method for producing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, the zeolitic material having in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element; 2and X 2 O 3 The molar ratio of is 16 to 175. (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, 8. The method of any one of the preceding claims, wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.

[0076] 9. The zeolitic material has a FAU framework structure type, preferably the zeolitic material is from the group consisting of Li-LSX, zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, SAPO-37, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof; Preferably from the group consisting of zeolite X, zeolite Y, ECR-30, ZSM-20, LZ-210, US-Y, CSZ-1, ZSM-3, faujasite, and mixtures of two or more thereof, More preferably, from the group consisting of zeolite X, zeolite Y, ZSM-20, ZSM-3, faujasite, and mixtures of two or more thereof, More preferably, the group consisting of zeolite X, zeolite Y, faujasite, and mixtures of two or more thereof. Contains one or more zeolites having a selected FAU-type framework structure, More preferably, the one or more zeolites having an FAU-type framework structure comprise zeolite X and / or zeolite Y, preferably zeolite Y; More preferably, the one or more zeolites having an FAU-type framework structure are zeolite X and / or zeolite Y, preferably zeolite Y. 9. The method according to any one of embodiments 1 to 8.

[0077] 10. The method of any one of the preceding embodiments, wherein the zeolitic material is in the ammonium or H form, more preferably in the H form.

[0078] 11. The zeolitic material is preferably adapted for temperature programmed desorption of ammonia (NH 3 11. The method according to any one of the preceding claims, comprising a concentration of acid sites in the range of 0.100 to 4.000 mmol / g at a temperature in the range of 190 to 550°C, more preferably a concentration of acid sites in the range of 0.200 to 2.000 mmol / g at a temperature in the range of 205 to 400°C, more preferably a concentration of acid sites in the range of 0.250 to 1.000 mmol / g at a temperature in the range of 250 to 290°C, more preferably a concentration of acid sites in the range of 0.300 to 0.800 mmol / g at a temperature in the range of 350 to 375°C, and more preferably a concentration of acid sites in the range of 0.400 to 0.700 mmol / g at a temperature in the range of 360 to 366°C, as determined by a pH-dependent spectrometry (TPD).

[0079] 12. The zeolitic material is preferably adapted for temperature programmed desorption of ammonia (NH 3 12. The method according to any one of the preceding claims, comprising a concentration of acid sites in the range of 0.050 to 0.600 mmol / g at a temperature in the range of 175 to 210 °C, preferably a concentration of acid sites in the range of 0.140 to 0.530 mmol / g at a temperature in the range of 185 to 200 °C, as determined by FT-TPD.

[0080] 13. The zeolitic material is preferably adapted for temperature programmed desorption of ammonia (NH 3 13. The method of any one of the preceding claims, comprising a concentration of acid sites in the range of 0.010 to 0.090 mmol / g at a temperature in the range of 475 to 625 °C, preferably a concentration of acid sites in the range of 0.030 to 0.060 mmol / g at a temperature in the range of 500 to 600 °C, as determined by FT-TPD.

[0081] 14. The method according to any one of the preceding embodiments, wherein the zeolitic material has a crystallinity in the range of 50-100% by weight, preferably 75-100% by weight, more preferably 80-100% by weight, more preferably 90-100% by weight, and the crystallinity is preferably determined as described in Example 3.

[0082] 15. The method of any one of the preceding embodiments, wherein the zeolitic material has a volumetric particle size distribution characterized by a Dv50 value in the range of 4.0 to 7.0 micrometers, preferably in the range of 4.5 to 6.5 micrometers, more preferably in the range of 5.0 to 6.0 micrometers.

[0083] 16. YO calculated as element Y 2 The method according to any one of embodiments 1 to 15, wherein the zeolitic material contains 35.0 to 47.0 wt %, preferably 38.5 to 43.5 wt %, more preferably 40.0 to 42.0 wt %, based on the total weight of the zeolitic material.

[0084] 17. X calculated as X 2 O 3 17. The method according to any one of embodiments 1 to 16, wherein the zeolitic material contains 1.0 to 4.5 wt. %, preferably 2.2 to 3.7 wt. %, more preferably 2.9 to 3.3 wt. %, based on the total weight of the zeolitic material.

[0085] 18. The zeolite material is preferably 380 ml, determined as described in Reference Example 1. 2 / g or more, preferably 650m 2 / g or more, more preferably 700 to 800m 2 18. The method of any one of the preceding claims, having a BET specific surface area in the range of 1 / g.

[0086] 19. The zeolite material is preferably determined as described in Reference Example 1, and the zeolite material is 500 ml 2 / g or more, preferably 800m 2 / g or more, more preferably 810 to 1100m 2 19. The method of any one of the preceding claims, having a Langmuir specific surface area in the range of 1 / g.

[0087] 20. The solid state of the zeolitic material, wherein X is Al, preferably determined as described in Reference Example 4. 27 20. The method of any one of the preceding embodiments, wherein Al NMR shows a peak in the range of 80-40 ppm and a peak in the range of 40-15 ppm, and the ratio of the peak integral of the peak in the range of 80-40 ppm to the peak integral of the peak in the range of 40-15 ppm is at least 3:1, more preferably at least 7:1, more preferably at least 10:1.

[0088] 21. The solid state of the zeolitic material, wherein X is Al, preferably determined as described in Reference Example 4. 27 21. The method of any one of the preceding embodiments, wherein Al NMR shows a peak in the range of 80-40 ppm and a peak in the range of 15-20 ppm, and the ratio of the peak integral of the peak in the range of 80-40 ppm to the peak integral of the peak in the range of 15-20 ppm is at least 3:1, preferably at least 7:1, more preferably at least 10:1.

[0089] 22. The method of any one of the preceding embodiments, wherein the zeolitic material has a micropore volume, preferably determined as described in Reference Example 1, in the range of 0.180 to 0.390 ml / g, preferably 0.220 to 0.350 ml / g, more preferably 0.260 to 0.310 ml / g.

[0090] 23. The method according to any one of the preceding embodiments, wherein the zeolitic material has an average pore diameter, preferably determined as described in Reference Example 1, in the range of 4.0 to 18.0 nm, preferably 5.5 to 8.0 nm, more preferably 6.6 to 7.3 nm.

[0091] 24. The method of any one of the preceding embodiments, wherein the zeolitic material has an average pore width, preferably determined as described in Reference Example 1, in the range of 1.5 to 5.5 nm, preferably 2.0 to 3.5 nm, more preferably 2.4 to 2.8 nm.

[0092] 25. The method according to any one of the preceding embodiments, wherein the zeolitic material provided in (i) is a calcined zeolitic material, and the zeolitic material has been calcined at a temperature in the range of 300 to 900°C, preferably 400 to 700°C, more preferably 450 to 650°C, more preferably 500 to 600°C.

[0093] 26. The process of embodiment 25, wherein the zeolitic material is calcined for a time period of 0.5 to 24 hours, preferably 1 to 15 hours, more preferably 2 to 12 hours, more preferably 2.5 to 9 hours, more preferably 3 to 7 hours, more preferably 3.5 to 6.5 hours, more preferably 4 to 6 hours.

[0094] 27. The method of any one of the preceding embodiments, wherein the catalyst is first contacted with acetone prior to contacting the catalyst with the reaction mixture of (ii).

[0095] 28. The method of any one of the preceding embodiments, wherein in (iii), the step of contacting the catalyst with the reaction mixture prepared in (ii) is carried out at a temperature in the range of 45 to 200°C, preferably 50 to 150°C, more preferably 55 to 120°C, more preferably 60 to 100°C, more preferably 65 to 90°C, more preferably 70 to 80°C.

[0096] 29. The method of any one of the preceding embodiments, wherein in (iii), the step of contacting the catalyst with the reaction mixture prepared in (ii) is carried out at a pressure in the range of 1 to 200 bar (abs), preferably in the range of 20 to 150 bar (abs), more preferably in the range of 30 to 100 bar (abs), more preferably in the range of 45 to 80 bar (abs), more preferably in the range of 50 to 70, more preferably in the range of 55 to 65 bar (abs).

[0097] 30. The method of any one of the preceding embodiments, wherein in (iii), the step of contacting the catalyst with the reaction mixture prepared in (ii) is carried out at a pressure in the range of 1 to 30 bar (abs), preferably in the range of 1 to 20 bar (abs), more preferably in the range of 1 to 15 bar (abs), more preferably in the range of 1 to 10 bar (abs), more preferably in the range of 1 to 5, more preferably in the range of 1 to 3 bar (abs).

[0098] 31. The method of any one of the preceding embodiments, carried out as a batch process or as a continuous process, preferably as a continuous process.

[0099] 32. The method of any one of the preceding embodiments, which is conducted as a continuous process and wherein the contacting step in (iii) is conducted at a liquid hourly space velocity (LHSV) in the range of 0.01 to 1000 ml / (g·h), preferably 0.05 to 500 ml / (g·h), more preferably 0.1 to 250 ml / (g·h), more preferably 0.3 to 100 ml / (g·h), more preferably 0.5 to 10 ml / (g·h), more preferably 1 to 5 ml / (g·h), more preferably 1.2 to 4 ml / (g·h), more preferably 1.5 to 3 ml / (g·h), more preferably 1.8 to 2.5 ml / (g·h), more preferably 2.0 to 2.2 ml / (g·h).

[0100] 33. (iv) separating 2,2,6,6-tetramethyl-4-piperidone from the reaction product to obtain 2,2,6,6-tetramethyl-4-piperidone and a residual mixture; (v) recycling at least a portion of the residual mixture in the reaction mixture of (ii). 33. The method of any one of the preceding embodiments, further comprising separating compounds having a boiling point higher than that of 2,2,6,6-tetramethyl-4-piperidone from the residual mixture, preferably after (iv) and before (v).

[0101] 34. The method of any one of the preceding embodiments, wherein in the reaction mixture prepared in (ii), the molar ratio of acetone to ammonia is in the range of 5:1 to 25:1, preferably in the range of 7:1 to 22:1, more preferably in the range of 10:1 to 19:1, more preferably in the range of 13:1 to 16:1, more preferably in the range of 14.0:1.0 to 14.7:1.0, more preferably in the range of 14.2:1.0 to 14.5:1.0.

[0102] 35. The method of any one of the preceding embodiments 1 to 34, which is conducted as a batch process, wherein the contacting step in (iii) is conducted for a period of time in the range of 0.1 to 24 hours, preferably in the range of 0.5 to 20 hours, more preferably in the range of 1 to 15 hours, more preferably in the range of 3 to 10 hours, more preferably in the range of 4 to 8 hours, more preferably in the range of 5 to 7 hours.

[0103] 36. The catalyst is provided as a molding, the molding being: (a) preparing a mixture comprising a zeolitic material and optionally one or more binders; (b) shaping the mixture, preferably by extrusion, to obtain a shaped material; (c) optionally drying the shaped material in a gas atmosphere; (d) sintering the shaped material obtained from (b) or (c) in a gas atmosphere to obtain a shaped product. 36. The method of any one of the preceding embodiments, wherein the compound is prepared according to a method comprising:

[0104] 37. The method of embodiment 36, wherein the mixture comprises one or more binders, and the one or more binders are one or more of alumina, silica, silica-alumina, graphite, polysaccharides, sugar alcohols, and synthetic polymers, preferably one or more of alumina, silica, silica-alumina, graphite, sugar alcohols, synthetic polymers, cellulose, modified cellulose, and starch, more preferably silica, alumina, silica-alumina, graphite, sugar alcohols, synthetic polymers, microcrystalline cellulose, cellulose ethers, more preferably graphite, sorbitol, mannitol, polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), hydroxypropyl cellulose (HPC), hydroxypropyl methylcellulose (HPMC), and sodium carboxymethylcellulose.

[0105] 38. The method of embodiment 36 or 37, wherein in the mixture according to (a), the weight ratio of the one or more binders to the zeolitic material is in the range of 1:10 to 1:30, more preferably in the range of 1:15 to 1:25.

[0106] 39. The method according to any one of embodiments 36 to 38, comprising a drying step according to (c), wherein the drying step is carried out in a gas atmosphere having a temperature in the range of 90 to 150°C, preferably at a temperature in the range of 110 to 130°C, for preferably 10 to 15 hours, more preferably 11 to 13 hours.

[0107] 40. The method according to any one of embodiments 36 to 39, wherein the gas atmosphere of (d) has a temperature in the range of 400 to 600 °C, preferably in the range of 450 to 550 °C, and preferably the calcination is carried out for 3 to 7 hours, more preferably 4 to 6 hours.

[0108] 41. The method of any one of embodiments 36 to 40, wherein the gas atmosphere in one or more of (c) and (d) comprises one or more of nitrogen, oxygen, and argon, preferably nitrogen. EXAMPLES

[0109] Reference example 1 BET specific surface area, Langmuir specific surface area, micropore volume, average pore width, and average pore diameter (N 2 ) Determination BET specific surface area, Langmuir specific surface area, micropore volume, average pore width, and average pore diameter (N 2 ) was determined by nitrogen physisorption at 77 K according to the method disclosed in DIN 66131.

[0110] Reference example 2 Determination of acid sites: Temperature programmed desorption of ammonia (NH 3 -TPD) Temperature programmed desorption of ammonia (NH 3 -TPD) was performed in an automatic chemisorption analysis unit (Micromeritics AutoChem II 2920) with a thermal conductivity detector. Continuous analysis of the desorbed species was performed using an online mass spectrometer (OmniStar QMG200 from Pfeiffer Vacuum). Samples (0.1 g) were introduced into a quartz tube and analyzed using the program described below. Temperature was measured by a Ni / Cr / Ni thermocouple located just above the sample in the quartz tube. He with a purity of 5.0 was used for the analysis. Before every measurement, a blank sample was analyzed for calibration.

[0111] 1. Preparation: Start recording, one measurement per second. 25°C and 30cm 3 Wait for 10 minutes at room temperature (approximately 25°C and 1 atm), heat to 600°C at a heating rate of 20 K / min, and maintain for 10 minutes. 3 / min) to 100 °C at a cooling rate of 20 K / min (furnace temperature gradient), and then cooled under a He flow (30 cm 3 / min) to 100 °C at a cooling rate of 3 K / min (sample temperature ramp). 2. NH 3 Saturation by: Start of recording, one measurement per second. Gas flow: 100 °C, 10% NH in He 3 (75cm 3 / min, 100°C, and 1 atm) and maintained for 30 min. 3. Remove excess: Start recording, take one measurement per second. Gas flow at 100°C, 75cm 3 / min (100°C and 1 atm) and maintained for 60 min. 4. NH 3 -TPD: Start of recording, one measurement per second. He flow (flow rate: 30 cm 3 / min) to 600 °C at a heating rate of 10 K / min and maintained for 30 min. 5. End of measurement.

[0112] The desorbed ammonia was measured by an online mass spectrometer, which demonstrated that the signal from the thermal conductivity detector was caused by the desorbed ammonia. This involved using the m / z=16 signal from ammonia to monitor the desorption of ammonia. The amount of adsorbed ammonia (mmol per g of sample) was ascertained by integrating the TPD signal with a horizontal baseline using Micromeritics software.

[0113] Reference example 3 Powder X-ray diffraction and crystallinity determination Powder X-ray diffraction (PXRD) data were collected using a diffractometer (D8 Advance Series II, Bruker AXS GmbH) equipped with a LYNXEYE detector operated with a copper anode X-ray tube operated at 40 kV and 40 mA. The geometry was Bragg-Brentano and air scattering was reduced using an air scattering shield.

[0114] Calculation of crystallinity: The crystallinity of the samples was determined using the software DIFFRAC.EVA supplied by Bruker AXS GmbH, Karlsruhe. The method is described in the user manual, page 121. Default parameters were used for the calculation.

[0115] Calculation of phase composition: The phase composition was calculated on the raw data using the modeling software DIFFRAC.TOPAS supplied by Bruker AXS GmbH, Karlsruhe. The crystal structure of the identified phases, the instrumental parameters, and the crystallite sizes of the individual phases were used to simulate a diffraction pattern. This was fitted to the data in addition to a function modeling the background intensity.

[0116] Data collection: Samples were homogenized in a mortar and then pressed into a standard flat sample holder supplied by Bruker AXS GmbH for Bragg-Brentano geometry data collection. A flat surface was obtained using a glass plate to compress and flatten the sample powder. The variable divergence slit was set at an angle of 0.1° and data were collected from an angular range of 2-70° 2θ with a step size of 0.02° 2θ. The crystalline content represents the intensity of the crystalline signal relative to the total scattered intensity. (User Manual for DIFFRAC.EVA, Bruker AXS GmbH, Karlsruhe).

[0117] Reference example 4 solid 27 Al NMR determination 27 Al solid-state nuclear magnetic resonance (NMR) was performed using the following device, procedure, and parameters: storage of samples for at least 60 hours at 62% relative humidity prior to packing; 3.2 mm ZrO with Vespel caps; 2 Loading of the sample into the rotor, Bruker Avance Neo spectrometer with 14.1 Tesla magnet, 15 kHz (ω / 2π) magic angle spinning, AlCl 3 Solution (1%, H2 One-pulse radio frequency excitation, corresponding to a 0.92 μs, 15° pulse in O; 10 ms acquisition of free induction decay, heterogeneous nuclei 1 H no high frequency decoupling, average of at least 5120 scans with 0.5 s recycle delay, Fourier transformation with 10 Hz exponential line broadening for noise suppression, manual phasing and baseline correction in Bruker Topspin 3.0. 37.77 ppm as secondary standard according to Pure Appl. Chem., Vol. 80, No. 1, pp. 59-84, 2008. 13 Using adamantane with a C methylene resonance, the frequency ratio of D is 0.26056859 on the absolute chemical shift scale. 2 1.1 mol / kg Al(NO 3 ) 3 The spectra were referenced to the standard.

[0118] Reference example 5 Properties of the tested zeolite materials

[0119] [Table 1]

[0120] [Table 2]

[0121] Example 1 Catalyst Testing – Batch Mode Catalysts 1 and 4, as well as comparative catalysts 1 and 3, were tested in batch mode as catalysts for the production of 2,2,6,6-tetramethyl-4-piperidone. In each test, an amount of 40 g (4 g / g) of catalyst was used. The temperature was set at 65° C. Each test was carried out for 6 hours, whereby ammonia was added for 1 hour before heating was started. The reaction products were analyzed by gas chromatography to determine the content of 2,2,6,6-tetramethyl-4-piperidone, 2,2,4,6-tetramethyl-2,3-dihydropyridine, 1,2,5,6-tetrahydro-2,2,4,6,6-pentamethyl-pyrimidine, and acetone. Thus, the results from gas chromatography measurements are shown in area %.

[0122] As can be inferred from the results shown in Table 3, Catalysts 1 and 4, which contain zeolitic materials with SARs of 25 and 20, respectively, show higher conversion to 2,2,6,6-tetramethyl-4-piperidone than Comparative Catalyst 3, which contains a zeolitic material with a SAR of 5.2. In particular, the relative amount of 2,2,6,6-tetramethyl-4-piperidone is higher in Catalysts 1 and 4 than in Comparative Catalyst 3 over the entire test period of 6 hours.

[0123] Furthermore, as can be seen in Table 3, the relative amounts of the undesirable by-product 2,2,4,6-tetramethyl-2,3-dihydropyridine, as determined by gas chromatography, are at relatively low levels for both Catalysts 1 and 4, as well as Comparative Catalyst 3. In summary, it can be seen from Table 3 that Catalysts 1 and 4 are the more active catalysts, particularly with respect to the conversion to 2,2,6,6-tetramethyl-4-piperidone.

[0124] As can be inferred from the results shown in Table 3, catalysts 1 and 4 show better catalytic performance compared to all comparative catalysts 1, and 3-6. In particular, the relative amount of 2,2,6,6-tetramethyl-4-piperidone is significantly higher in catalysts 1 and 4, and therefore the relative amount of the undesired by-product 2,2,4,6-tetramethyl-2,3-dihydropyridine is significantly lower than comparative catalyst 4 and comparable to comparative catalyst 1. It can be further seen in Table 3 that the relative amount of 1,2,5,6-tetrahydro-2,2,4,6,6-pentamethyl-pyrimidine is significantly lower in catalysts 1 and 4, and the overall conversion of acetone is also higher in catalysts 1 and 4 compared to all comparative catalysts 1, and 3-6.

[0125] Furthermore, it can be seen in Table 3 that the ratio of 2,2,6,6-tetramethyl-4-piperidone:2,2,4,6-tetramethyl-2,3-dihydropyridine is significantly higher in catalysts 1 and 4 compared to comparative catalysts 1, and 3-6.

[0126] In addition, it can be inferred from Table 3 that Comparative Catalyst 6, which comprises a zeolitic material having an MFI framework structure and a silica to alumina molar ratio (SAR) of 30, exhibits an overall inferior performance compared to Catalysts 1 and 4.

[0127] [Table 3]

[0128] The characteristics of the zeolite materials tested are set out in Tables 1 and 2 above.

[0129] Example 2 Catalyst Testing - Continuous Mode Catalyst 2 and Comparative Catalyst 2 were tested in continuous mode as catalysts for the production of 2,2,6,6-tetramethyl-4-piperidone. A reactor with a length of 1 m and a diameter of 8 mm was used. The reactor wall temperature was set at 70° C., the liquid hourly space velocity at 1.71 ml / gh, and the pressure at about 55 bar (single phase). The feed stream contained acetone and ammonia in a molar ratio of 14.3:1.0. Each test was carried out for 6 hours. The average residence time was found to be about 60-74 minutes.

[0130] In the catalytic test in continuous mode, each catalyst was used as a shaped body. To this effect, 1250 g of each zeolite material, 1180 ml of deionized water and 62.5 g of Walocel (Walocel MW 15000 GB, Wolff Cellulosics GmbH & Co. KG, Germany) were fed into a kneader and kneaded for 10 minutes. For shaping, the kneaded mass was extruded at a pressure of 190 bar (abs) to obtain strands with a circular cross section with a diameter of 1.5 mm. The strands were then dried at 120° C. for 12 hours and calcined at 500° C. for 5 hours. The reaction products were analyzed by gas chromatography to determine the content of 2,2,6,6-tetramethyl-4-piperidone, 2,2,4,6-tetramethyl-2,3-dihydropyridine, 1,2,5,6-tetrahydro-2,2,4,6,6-pentamethyl-pyrimidine and acetone, and the results from gas chromatography are given in area %.

[0131] As can be inferred from the results shown in Table 4, Catalyst 2 shows a higher conversion to 2,2,6,6-tetramethyl-4-piperidone compared to Comparative Catalyst 2, even in continuous mode. As can be seen in Table 4, the ratio of 2,2,6,6-tetramethyl-4-piperidone:2,2,4,6-tetramethyl-2,3-dihydropyridine is higher in Catalyst 2 than in Comparative Catalyst 2. This finding is all the more surprising because, as discussed above, the prior art Cavani et al. suggests the use of HY zeolite, which has a relatively low SAR of 6, in particular, as it shows the best results in terms of preparing the desired 2,2,6,6-tetramethyl-4-piperidone and produces the least undesirable by-product 2,2,4,6-tetramethyl-2,3-dihydropyridine. In comparison, HY zeolite with SAR of 15, tested by Cavani et al. in Journal of Molecular Catalysis A: Chemical 393 (2014), 325-332, showed relatively poor performance in terms of the preparation of 2,2,6,6-tetramethyl-4-piperidone and in terms of the by-products. Similarly, J. Tian et al. in Journal of Heterocyclic Chemistry 2015, vol. 52, pp. 1377-1381, found that HY zeolite with a silica to alumina molar ratio of 11.2 was the most effective in the preparation of 2,2,6,6-tetramethyl-4-piperidone, as discussed above. Apparently, J. Tian considered the zeolite with a relatively low SAR to be the most promising for further experiments, especially with regard to acetone optimization of the applied reaction conditions. In contrast thereto, especially taking into account the process mode according to the invention which tolerates only limited contents of water, the method according to the invention involving zeolitic materials having an FAU framework structure type surprisingly also shows technical effects for zeolitic materials having a relatively high silica to alumina ratio.

[0132] The characteristics of the zeolite materials tested are set out in Tables 1 and 2 above.

[0133] [Table 4] Aspects of the present disclosure include the following. [1] A method for producing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, the zeolitic material having in its framework structure YO 2 and X 2 O 3 wherein Y is a tetravalent element and X is a trivalent element; 2 and X 2 O 3 The molar ratio of is 16 to 175. (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, The process wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture. [2] 2. The method of embodiment 1, wherein greater than or equal to 5 wt.% of the catalyst consists of zeolitic material. [3] 3. The method of any one of the preceding aspects, wherein the catalyst is provided as a powder and / or as a moulded product. [4] 4. The method of any one of the preceding aspects, wherein Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and mixtures of two or more thereof. [5] 5. The method of any one of the preceding aspects, wherein X is selected from the group consisting of B, Al, Ga, In, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and mixtures of two or more thereof. [6] Aspects 6. The method of any one of aspects 1 to 5, wherein the zeolitic material is in the ammonium or H form. [7] 7. The method according to any one of the preceding aspects, wherein the zeolitic material has a crystallinity in the range of 50-100 wt.%, the crystallinity being determined as described in Example 3. [8] YO calculated as element Y 2 The method according to any one of aspects 1 to 7, wherein the zeolitic material contains is in the range of 35.0 to 47.0 wt %, based on the total weight of the zeolitic material. [9] X calculated as X 2 O 3 The method according to any one of aspects 1 to 8, wherein the zeolitic material contains is present in an amount of 1.0 to 4.5 wt %, based on the total weight of the zeolitic material.

[10] 10. The method of any one of the preceding aspects, wherein in (iii), the step of contacting the catalyst with the reaction mixture prepared in (ii) is carried out at a temperature in the range of 45 to 200° C.

[11] 11. The method according to any one of the preceding aspects, carried out as a batch process or as a continuous process.

[12] 12. The method of any one of the preceding aspects, wherein in the reaction mixture prepared in (ii), the molar ratio of acetone to ammonia is in the range of 5:1 to 25:1.

[13] The catalyst is provided as a molding, the molding being (a) preparing a mixture comprising a zeolitic material and optionally one or more binders; (b) shaping the mixture; (c) optionally drying the shaped material in a gas atmosphere; and (d) sintering the shaped material obtained from (b) or (c) in a gas atmosphere to obtain a shaped product. 13. The method according to any one of the preceding aspects, wherein the compound is prepared according to a method comprising the steps of:

Claims

1. A method for producing 2,2,6,6-tetramethyl-4-piperidone, comprising the steps of: (i) providing a reactor containing a catalyst comprising a zeolitic material having a framework structure of FAU, the zeolitic material having in its framework structure YO 2 and X 2 O 3 wherein Y is Si and X is a trivalent element selected from the group consisting of B, Al, Ga, and mixtures of two or more thereof; and the zeolitic material Y 2 and X 2 O 3 is 16 to 80 in mole ratio; (ii) preparing a reaction mixture comprising acetone and ammonia; (iii) contacting a catalyst in a reactor with the reaction mixture prepared in (ii) at a temperature in the range of 40 to 250° C. to obtain a reaction product comprising 2,2,6,6-tetramethyl-4-piperidone. Including, The process wherein the mixture prepared in (ii) and contacted with the catalyst in (iii) contains less than 10 wt.-% water, based on 100 wt.-% of the reaction mixture.

2. 10. The method of claim 1, wherein at least 5% by weight of the catalyst consists of the zeolite material.

3. 3. The method according to claim 1 or 2, wherein the catalyst is provided as a powder and / or as a moulded product.

4. 4. The method of claim 1, wherein X is Al.

5. 5. The method of claim 1, wherein the zeolitic material is in the ammonium or H form.

6. 6. The method according to any one of claims 1 to 5, wherein the zeolitic material has a crystallinity in the range of 50 to 100 wt%, the crystallinity being determined as described in Example 3.

7. YO calculated as element Y 2 The method according to any one of claims 1 to 6, wherein the zeolitic material is contained in an amount of from 35.0 to 47.0 wt % based on the total weight of the zeolitic material.

8. X calculated as X 2 O 3 The method according to any one of claims 1 to 7, wherein the zeolitic material is contained in an amount of from 1.0 to 4.5 wt % based on the total weight of the zeolitic material.

9. 9. The process according to any one of claims 1 to 8, wherein in (iii), the step of contacting the catalyst with the reaction mixture prepared in (ii) is carried out at a temperature in the range of 45 to 200°C.

10. 10. The process according to any one of claims 1 to 9, carried out as a batch process or as a continuous process.

11. 11. The process according to any one of claims 1 to 10, wherein in the reaction mixture prepared in (ii), the molar ratio of acetone to ammonia is in the range of 5:1 to 25:

1.

12. The catalyst is provided as a molding, the molding being (a) preparing a mixture comprising a zeolitic material and optionally one or more binders; (b) shaping the mixture; (c) optionally drying the shaped material in a gas atmosphere; and (d) sintering the shaped material obtained from (b) or (c) in a gas atmosphere to obtain a shaped product.

12. The method according to any one of claims 1 to 11, wherein the composition is prepared according to a method comprising:

Citation Information

Patent Citations

  • Method and special device for heterogeneous catalyzed synthesis of triacetonamine

    CN107033066A

  • 2,2,6,6-tetramethylpiperidone synthesis method for setting end-point determination mode

    CN107915673A

  • Process for the preparation of 2,2,6,6-tetramethyl-piperidone-(4)

    EP0004104A2

  • Method for producing 2,2,6,6-tetrametyl-4-piperidone

    JP2003252858A

  • Method for synthesizing 2,2,6,6-tetramethyl-4-oxopiperidine

    JP2004525081A